Listeria Occurrence and Potential Control Strategies in Alternative and Conventional Poultry Processing and Retail - Rothrock, Michael J.; Micciche, Andrew C.; Bodie, Aaron R.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2019)
Listeria monocytogenes is a psychrotrophic Gram positive organism that is considered one of the more critical foodborne pathogens of public health concern. To prevent illness the USDA and FDA enforce a zero-tolerance policy for Listeria on ready-to-eat foods such as delicatessen meats and poultry. Regardless, L. monocytogenes can still be isolated from food production facilities and retail products, indicating that current sanitation methods are not always sufficient. Both conventional and alternative poultry production and processing systems have also been identified as potential sources of Listeria. Concerns associated with alternative poultry production and processing can be further exacerbated by limitations on sanitation and available antimicrobials for usage in organic and natural poultry products. Furthermore, mobile poultry processing units often process organic and small-scale poultry farms that are not able to be processed by conventional standing facilities. These alternative production facilities and their products are often exempt from federal inspection, due to processing a relatively low number of carcasses. Due to these exemptions, it is unknown if sufficient sanitation is applied in these alternative processing facilities to prevent L. monocytogenes contamination. Organic processing restrictions may also impact which sanitizers and antimicrobials can be utilized. This review describes variations between conventional and mobile poultry processing units in conjunction with how L. monocytogenes may persist in the processing environment and on retail products. This review will also examine alternative antimicrobials proven to be effective against Listeria and potentially be acceptable for use in alternative poultry production systems.